Graphite with Different Structures as Catalysts for Counter Electrodes in Dye-sensitized Solar Cells. (10th October 2015) - Li, Yu-Yan; Li, Chun-Ting; Yeh, Min-Hsin; Huang, Kuan-Chieh; Chen, Ping-Wei; Vittal, R.; Ho, Kuo-Chuan
Graphical Abstract: Highlights: Low cost graphites were used as counter electrodes in dye–sensitized solar cells. Graphite nanofiber (GNF), nanosheet (GNS) and nanoball (GNB) were used. Among them, GNB has the most amounts of inner defects and largest surface area. The GNB gave a good electro-catalytic ability and a cell efficiency of 7.88%. GNB can replace Pt owing to its low-cost and good catalytic ability. Abstract: Three graphite materials with different structures, including graphite nanofiber (GNF), graphite nanosheet (GNS), and graphite nanoball (GNB), were used as the catalytic films on the counter electrodes (CEs) of dye–sensitized solar cells (DSSCs). Compared to GNF and GNS, GNB not only provides a higher degree of defects in the sp 2 plane structure but also possesses aboundant hydroxyl functional groups as the electro-catalytic active sites for I3 − reduction; thereby, the intrinsic heterogeneous rate constant ( k0 ) and effective electro-catalytic surface area ( A e ) of GNB-based CE are both higher than the values of GNF-based and GNS-based CEs. The GNB-based DSSC with showed the power conversion efficiency ( η ) of 7.88%, while those GNF-based and GNS-based DSSCs showed η 's of 3.60% and 2.99%, respectively. Moreover, it is also observed that the η of the GNB-based DSSC (7.88%) is quite close to that of a Pt-based DSSC ( η =8.38%); this implies that the GNB can become a potential candidate to replace the expensive Pt, owing to its low-cost.